Neurocognitive functioning and outcome of the Illness Management and Recovery Program for clients with schizophrenia and schizoaffective disorder. (17th August 2016) - Färdig, Rickard; Fredriksson, Anders; Lewander, Tommy; Melin, Lennart; Mueser, Kim T.
Abstract: The relationship between psychosocial programming and neurocognition has been established in previous research, but has not been explored in the context of the Illness Management and Recovery Program (IMR). This study examined associations between neurocognition and illness self-management skills acquisition, based on two previous trials of IMR. Neurocognitive functioning was assessed at baseline and post-treatment in 53 participants with schizophrenia or schizoaffective disorder who completed the IMR. Illness self-management was measured by the client and clinician versions of the Illness Management and Recovery Scale. Statistical analyses investigated improvements in neurocognitive functioning and possible association between illness self-management skills acquisition and neurocognitive functioning. Speed of processing as measured by the Trail Making Test A, was related to client-reported acquisition of illness self-management skills, before and after controlling for psychiatric symptoms and medication, but did not predict improvement in clinician ratings of client illness self-management skills. However, when controlling for client session attendance rates, the association between speed of processing and client-reported illness self-management skills acquisition ceased to be statistically significant, which suggests that compromised neurocognitive functioning does not reduce response to training in illness self-management in itself. The association between the frequency of attended IMR sessions and outcome of the IMR seems to decrease the negative impact of compromised neurocognition on illness self-management skills acquisition. Also, clients with slower speed of processing may experience less benefit from the IMR and may attend fewer sessions.